Conceptual Framework: Emotional Intelligence and Social Media for Health and Medical Tourism - David Groves; Katey Price; Fang Wang (Visions in Leisure and Business)
Social media technologies have played a significant role in most people's lives in recent years. It has significantly changed the way we do business, form relationships, etc. The health and tourism industry has been significantly changed with the new technologies. It is not only from a client perspective, but also from infrastructural relationships among administrators, doctors, nurses, etc. This is also greatly reflected from a cultural perspective. It is obvious that two of the outstanding elements in helping to understand the impacts of social media are cognitive and emotional factors. Emotional factors play a significant role in social media, and it was the purpose of this study to examine critical elements in relation to health and medical tourism. The primary focus was to review significant studies and develop a working model to help develop a greater understanding about the mechanisms of social media in relation to health and medical tourism. The primary element that started this study was from client interviews and the apparent emotional context and its influence upon individuals’ decisions.